Green segmentation: a cross-national study - Yilmazsoy, Baris; Schmidbauer, Harald; Roesch, Angi (Emerald Group Publishing Ltd, 2015)
Purpose - Understanding and defining the characteristics of environmentally conscious or concerned consumers has received attention from academic researchers, commercial sector, and policy makers. The purpose of this paper is to identify distinct market segments in three countries ( China, Germany, and Turkey) based on several green attitude and behavior variables. Design/methodology/approach - A survey was administered in three countries, yielding a total of 1,415 valid survey responses. Findings - Four clusters, ranging from the greenest to the least green segment, were identified and characterized for each country. Inter-and intra-country similarities and differences are discussed. Existence of cross-national segments was confirmed. Research limitations/implications - There is a potential gap between actual behavior and reported behavior. Practical implications - The segment profiles can be valuable to firms, particularly to those competing in multinational markets. By delineating areas of similarity among international diversity, enterprises can develop effective global marketing strategies. Social implications - Understanding market segments in this respect is critical for policy makers who try to focus their policies that seek to promote green consumption. Originality/value - This is the first study that uses cross-national data for segmenting the market based on green criteria, to the authors' knowledge. Methodologically, the paper uses techniques and instruments that have not been used in this context before.
Keywords: China; Germany; Green Marketing; Market Segmentation; Cross-Cultural Research; International Marketing; Turkey; Market-Segmentation; Environmental Concern; Ecological Paradigm; Socio-Demographics; Consumer; Behavior; Attitudes; Locus